Wittgenstein on string figures as mathematics: A modern ethnological approach to the limits of empiricism. (16th August 2022) - English, Andrew
Abstract: Wittgenstein's 'ethnological approach' to the philosophy of mathematics, in particular his discussion of calculation as an experiment and the limits of empiricism in mathematics, is presented against three interrelated backdrops: (1) James' critique of Spencer's evolutionary empiricism, specifically regarding necessary truths; (2) the Cambridge Anthropological Expedition to Torres Straits, led by Haddon and Rivers, whose Reports implicitly confuted Spencer; and (3) the subsequent work of Malinowski, especially his supplement to Ogden and Richards' The Meaning of Meaning, a book sent to Wittgenstein upon its publication in 1923. String figures as mathematics is a main illustrative example.